Free Triiodothyronine in Hemodialysis Patients: Link With Malnutrition and Inflammation (Iranian Journal of Kidney Diseases, 2014)
Introduction. Free triiodothyronine (FT3) is a marker of comorbidity in end-stage renal disease and in many acute and chronic diseases. There is lack of data about the link between FT3 levels and malnutrition and inflammation in hemodialysis patients. The objective of the present study was to investigate the link between FT3 and malnutrition and inflammation in hemodialysis patients. Materials and Methods. A total of 84 patients were included in the study (38 men and 46 women; mean age, 56.2 ± 14.8 years; hemodialysis duration, 95.72 ± 10.35 months). Serum FT3, free thyroxin, and thyroid-stimulating hormone concentrations were determined. Demographic data and laboratory values were evaluated. Patients' comorbidity status was determined using the Charlson Comorbidity Index (CCI), and malnutrition-inflammation status was determined by Malnutrition-Inflammation Score (MIS). Results. Serum FT3 concentration inversely correlated with age (r = -0.328, P = .002), CCI (r = -0.591, P < .001), C-reactive protein (r = -0.299, P = .01), and MIS (r = -0.671, P < .001), and positively correlated with serum albumin (r = 0.389, P < .001). In multivariate linear regression analysis, FT3 was independently associated with MIS (β, -0.14; 95% confidence interval, -0.175 to 0.063, P = .003), adjusted for CCI, C-reactive protein level, serum albumin level, and MIS. Conclusions. The results of this study indicate that FT3 is negatively correlated with inflammatory markers, namely C-reactive protein, and it is independently related with MIS in hemodialysis patients. Therefore, we suggest that FT3 can be accepted as an inflammatory marker in hemodialysis patients.